Congenital hyperinsulinism: current status and future perspectives - Tohru Yorifuji (Korean Society of Pediatric Endocrinology, 2014)
The diagnosis and treatment of congenital hyperinsulinism (CHI) have made a remarkable progress over the past 20 years and, currently, it is relatively rare to see patients who are left with severe psychomotor delay. The improvement was made possible by the recent developments in the understanding of the molecular and pathological basis of CHI. Known etiologies include inactivating mutations of the KATP channel genes (ABCC8 and KCNJ11) and HNF4A, HNF1A, HADH, and UCP2 or activating mutations of GLUD1, GCK, and SLC16A1. The understanding of the focal form of KATP channel CHI and its detection by 18F-fluoro-L-DOPA positron emission tomography have revolutionized the management of CHI, and many patients can be cured without postoperative diabetes mellitus. The incidence of the focal form appears to be higher in Asian countries; therefore, the establishment of treatment systems is even more important in this population. In addition to diazoxide or long-term subcutaneous infusion of octreotide or glucagon, long-acting octreotide or lanreotide have also been used successfully until spontaneous remission. Because of these medications, near-total pancreatectomy is less often performed even for the diazoxide-unresponsive diffuse form of CHI. Other promising medications include pasireotide, small-molecule correctors such as sulfonylurea or carbamazepine, GLP1 receptor antagonists, or mammalian target of rapamycin inhibitors. Unsolved questions in this field include the identification of the remaining genes responsible for CHI, the mechanisms leading to transient CHI, and the mechanisms responsible for the spontaneous remission of CHI. This article reviews recent developments and hypothesis regarding these questions.